Land tenure and economic activities in Uganda: A literature review - Rasmus Hundsbæk Pedersen; Rachel Spichiger; Sarah Alobo; Michael Kidoido; Bernard Bashaasha; Helle Munk Ravnborg (Danish Institute for International Studies (DIIS), 2012)
Land is an important asset for people's livelihoods and for economic development in Uganda, where the majority of people live in rural areas. This working paper reviews the literature on Uganda's tenure systems and their relationship with economic activities, focusing primarily on rural agricultural land. The review illustrates that these relationships are complex and context-dependent. Uganda's land reform was introduced with the 1998 Land Act which aims at enhancing tenure security by recognising existing rights to land. It also aims at bringing land onto the market. However, the reform's implementation has been slow and partial so far. The division of labour between land administration institutions is unclear and often institutions, for instance dispute settlement institutions, are inaccessible at the local level. Furthermore, the evidence of any links between the formalisation of land rights, investment and productivity under different tenure systems is inconclusive. Land markets exist irrespective of the tenure systems. Access to credit is quite limited, and not primarily linked to titled land as some scholars suggest. Regional differences, the urban/rural divide and social and gender characteristics are equally important. This review shows, however, that tenure insecurity, in particular in the postconflict context of northern Uganda, discourages investment and leads to lower productivity. A likely path to strengthening agricultural production would be the reinforcement of dispute settlement institutions. Furthermore, despite a gender-sensitive legal framework, women have been discriminated against in both the customary and statutory settings. Improving women's access to land would also seem important. Overall, more systematic research on these issues is required.
Keywords: 300; Bodenrecht; Bodenreform; Agrarproduktion; Geschlechterdiskriminierung; Bibliometrie; Uganda